PENGARUHPENDEKATANKONSTRUKTIVISMETERHADAP HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 11 JAYAPURAPADA POKOKBAHASAN GETARAN DAN GELOMBANGTAHUN AJARAN 2012/2013 - INDAH SLAMET BUDIARTI; ALBERT LUMBU; DWI SULISTIOWATI (Jurnal Ilmu Pendidikan Indonesia, 2018)
This research was made to know the relation and the influence of constructive approach to the learning result of students in grade 8th SMP N 11 Jayapura for the vibration  and wave lesson of 2012/2013 academic year. This research is quantitative research. The population of this research are all of grade 8th students of SMP N 11 Jayapura. The technique of data collection that used is purposive sampling, with 32 students as the sample to know the relationship between the constructive approach with the learning result, correlation analysis has been used to prove it with the result tcount > ttable, equal 4.044 > 2.042, it means there’s any relationship between constructive approach to the learning result, while to know the influence between constructive approach to the learning result, regressive analysis has been applied with the result Fcount> Ftable , equal 16.358 > 4.17, it means there’s an influence between the constructive approach to the learning result of the students. Key word: constructive approach, the learning result.